Developing a socio-psychological model explaining farmers' income diversification in response to groundwater scarcity in Iran. Issue 2 (4th March 2022) - Hashemi, Seyyed Mahmoud; Kinzig, Ann; Eakin, Hallie; Abbott, Joshua K.; Sedaghat, Reza
ABSTRACT: Income diversification is an essential livelihood strategy for farmers facing unsustainable groundwater withdrawals. This paper develops a general structural equation model that analyses socio-psychological factors that affect the intentions to adopt and the actual adoption of income diversification in response to groundwater scarcity. The developed model includes affective attitudes, instrumental attitudes and self-efficacy. This model explains 55% and 36% of the variance in intentions to pursue and the actual pursuit of income diversification among farmers in the Rafsanjan Plain, Iran, respectively. These results can inform policies for promoting income diversification, and have implications for sustaining farmers' livelihoods and groundwater resources.